PERSEVERING FOR A CRUEL AND CYNICAL FICTION? THE EXPERIENCES OF THE 'LOW ACHIEVERS' IN PRIMARY SCHOOLING. Issue 4 (4th July 2022) - Hargreaves, Eleanore; Quick, Laura; Buchanan, Denise
ABSTRACT: This paper is significant in its exploration of the experiences of children designated as 'lower-attaining' in British primary schooling. It is underpinned by Nancy Fraser's conceptualisation of a global shift from government via nation-state welfare structures to governance through supra-national financialised neoliberalism. Within this context, we take the innovative path of investigating how 'lower-attaining' children explain perseverance with hard work at school within neoliberalism's 'cruel and cynical fiction' of social mobility. Our extended interviews with 23 'lower-attaining' children over two years provide findings which indicate – with a startling vividness – that these particular children experienced loneliness at school and blamed themselves for being inadequate and inferior. Fear appeared to be an essential component of their schooling system and sometimes elicited from them anger as well as humiliation. In particular, these children feared being assessed and sorted according to attainment. We propose that these factors often led the 'lower-attaining' children to experience schooling as at least uncomfortable. And yet they came to accept as fact the fiction that they were inadequate; and to perceive that perseverance in conforming to schooling's rules was their only chance of not slipping out of the race altogether.